Starting Online Services at University Clinics at the Beginning of the Covid-19 Pandemic - Dhanasari Vidiawati Trisna; Riri Indriyanti; Mora Claramita (Faculty of Medicine, Public Health, and Nursing, 2020)
The UI Makara Satellite Clinic (KSUI) is a university clinic that serves UI residents and the public as well as a vehicle for education and health research in primary services. It has been a BPJS Outpatient Service Clinic (KPRJ) since October 2018. It is called a Satellite Clinic because it is planned to become a satellite for university hospitals in the academic health system at the University of Indonesia. Currently, KSUI is located on the Depok campus and the Salemba campus. In its daily services at the Depok campus, KSUI provides services for doctors, dentists, nursing, pharmacy, laboratories, action rooms, and psychological counseling.KSUI’s mission is not the same as an ordinary outpatient clinic, but because KSUI is a health service facilitated by the university, KSUI has a mission to maintain the health of the academic community, and not only treat them when they fall ill. Therefore, in addition to services that respond to patients coming to the clinic, KSUI also organizes periodic health check services, facilitates Posbindu activities in the faculties and office buildings on campus, and participates in medical care at any gathering or sports activities provided on campus.With the Covid-19 case being found in Indonesia, KSUI decided to change its service method as quickly and as firmly as possible from face-to-face services to online services, following the Chancellor’s Decree to close the campus from face-to-face learning and other student activities. With the return of the UI dormitory students and the implementation of work from home (WFH) for lecturers and education staff, KSUI must provide safe services during a pandemic and can be accessed by service users without having to come to campus. Therefore, this article is a brief piece of information that has been done by KSUI when it decided that services should be carried out online. It is not easy for the officer, because it has never been done, and it is not easy for the patient.